Wilks’ Factorization of the Complex Matrix Variate Dirichlet Distributions - Cui, Xinping; K. Gupta, Arjun; K. Nagar, Daya (Revista Matemática Complutense, 2005)
In this paper, it has been shown that the complex matrix variate Dirichlet type I density factors into the complex matrix variate beta type I densities. Similar result has also been derived for the complex matrix variate Dirichlet type II density. Also, by using certain matrix transformations, the complex matrix variate Dirichlet distributions have been generated from the complex matrix beta distributions. Further, several results on the product of complex Wishart and complex beta matrices with a set of complex Dirichlet type I matrices have been derived.